Permainan Edukasi sebagai Media Pembelajaran Bahasa Inggris bagi Siswa Madrasah Ibtidaiyah - Maulida Fairuz Salsabila; Irma Nur Af'idah; M. Sofyan Alnashr (Mafa Press in Collaboration with PGMI Tarbiyah Faculty IPMAFA, 2023)
English is one of the important subjects that students must learn so that teachers need to be creative in presenting the material and learning media. This study aims to develop educational games based on power point as a learning media for grade 1 students of MI Al-Hikmah Kajen on English alphabet material. The type of research used is R & D (Research and Development) model Borg and Gall. The population of this study were all grade 1 students of MI Al-Hikmah Kajen, totaling 46 students. The results of the research on the development of educational games based on power point are able to make all students enthusiastic in learning, and make students able to understand better the alphabet material delivered with learning media. The results of the feasibility test for the validation stage and the teacher questionnaire obtained an average score of 4 in the Good category. While the questionnaire distributed to students obtained an average score of 5 with a very good category. The results of this validation indicate that the learning media made are very feasible to use as teaching materials at MI Al-Hikmah Kajen.